2012
DOI: 10.1016/j.neuroscience.2012.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and innervation of the vestibular lagena in pigeons

Abstract: The morphological characteristics of the pigeon lagena were examined using histology, scanning electron microscopy, and biotinylated dextran amine (BDA) neural tracers. The lagena epithelium was observed to lie partially in a parasagittal plane, but was also U-shaped with orthogonal (lateral) directed tips. Hair cell planar polarities were oriented away from a central reversal line that ran nearly the length of the epithelium. Similar to the vertebrate utricle and saccule, three afferent classes were observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
(119 reference statements)
0
8
0
Order By: Relevance
“…However, the exact mechanisms how the Earth's magnetic field is perceived and processed is only starting to be understood. Currently, three main magnetoreception hypotheses are discussed: a light-dependent chemical compass sense associated with the visual system [3][4][5][6][7][8][9][10], a recently suggested involvement of the vestibular system [11][12][13][14][15] but see [16], and an iron-mineral-based sense located in the upper beak [17][18][19][20]. The last hypothesis was associated with claims of the existence of iron-mineral structures in six defined dendritic fields within the subepidermal layer of the upper beak [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…However, the exact mechanisms how the Earth's magnetic field is perceived and processed is only starting to be understood. Currently, three main magnetoreception hypotheses are discussed: a light-dependent chemical compass sense associated with the visual system [3][4][5][6][7][8][9][10], a recently suggested involvement of the vestibular system [11][12][13][14][15] but see [16], and an iron-mineral-based sense located in the upper beak [17][18][19][20]. The last hypothesis was associated with claims of the existence of iron-mineral structures in six defined dendritic fields within the subepidermal layer of the upper beak [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The basic shape of the lagena is taken from curve fits of the morphology [18] redrawn in Fig.1A. Hair cells external to the socalled line-of-reversal (green dashed line) are oriented towards the longer rim (pars externa), and vice versa.…”
Section: Methodsmentioning
confidence: 99%
“…It is one of three otolithic sense organs in the inner ear and detects linear accelerations (Zakir et al . ). Following on from the observation that the lagena contains iron‐rich otoliths (Harada et al .…”
Section: Magnetoreceptionmentioning
confidence: 97%
“…The lagena is a vestibular sense organ located at the distal tip of the basilar papilla; it is present in birds, but absent in mammals. It is one of three otolithic sense organs in the inner ear and detects linear accelerations (Zakir et al 2012). Following on from the observation that the lagena contains iron-rich otoliths (Harada et al 2001), behavioral experiments demonstrated that lagena removal, or the insertion of small magnets into the inner ear, compromised the navigational abilities of homing pigeons (Harada 2002).…”
Section: Inner-ear Magnetoreceptorsmentioning
confidence: 99%